1988
DOI: 10.1159/000138425
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-Mediated Action of Sennosides

Abstract: The aim of this study was to investigate whether prostaglandins (PG) are involved in the mediation of sennoside-induced colonic fluid and electrolyte secretion. Oral administration of senna pod extract dose-dependently reversed net absorption of water, sodium and chloride to net secretion, increased potassium secretion and stimulated the release of PGE2 into the colonic lumen. Inhibition of PG biosynthesis by pretreatment of the rats with indometacin significantly inhibited the effects of senna pod … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The laxative effect of senna or sennosides is mediated by their dual effects on intestinal fluid transport and on intestinal motility [1,10,11]. We showed that rhein anthrone stim ulates both large intestinal fluid transport and large intestinal transit [4], This led us to examine the effects of these pretreatments on the fluid and electrolyte transport and large intestinal transit.…”
Section: Discussionmentioning
confidence: 99%
“…The laxative effect of senna or sennosides is mediated by their dual effects on intestinal fluid transport and on intestinal motility [1,10,11]. We showed that rhein anthrone stim ulates both large intestinal fluid transport and large intestinal transit [4], This led us to examine the effects of these pretreatments on the fluid and electrolyte transport and large intestinal transit.…”
Section: Discussionmentioning
confidence: 99%
“…Several media tors have been postulated to be involved in the sennoside-induced stimulation of active chloride secretion and hence fluid secretion into the intestinal lumen, such as prostaglan dins [2], histamine and serotonin [3] and Ca2+ In the present investigation the importance rf 5-HT in sennoside-induced secretion is ;onfirmed. Ketanserin, an antagonist at 5-rlTj receptors, and tropisetron, a 5-HT3 re-:eptor antagonist, reduced the secretory effect )f a medium dose of sennosides, granisetron, m antagonist at 5-HTj receptors which is nore selective in its action than tropisetron since it has no effect on 5-HT4 receptors, :otally abolished sennoside-induced colonic luid secretion.…”
Section: Discussionmentioning
confidence: 50%
“…The effects seem to be independent from each other and show a different time course [1]. Both the secretory and the large intestinal propulsive effect of sennosides appear to involve prostaglandin E2 (PGE2) [1,2]. Sennosides stimulate PGE2 re lease into the colonic lumen and the effects on secretion and on motility are reduced by PG biosynthesis inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that AQs act by disturbing the equilibrium between the absorption of water from the intestinal lumen via an active sodium transport [10] and the secretion of water into the lumen by the hydrostatic blood pressure or a prostaglandin-dependent chloride secretion [11,12]. Anthrones, formed from AQs or their glycosides via reduction by the intestinal flora are most likely the active metabolites [13].…”
Section: Pharmacology and Usesmentioning
confidence: 99%